Fixed Point Theorems for Set-Valued L-Contractions in Branciari Distance Spaces - Seong-Hoon Cho (Abstract and Applied Analysis)
In this paper, the notion of set-valued L-contractions is introduced, and a new fixed point theorem for such contractions is established. An example to illustrate main theorem is given.